Anatomical Basis of Dynamic Modulation of Tympanic Tension in the Water Monitor Lizard, Varanus salvator. Issue 9 (13th July 2016) - Han, Dawei; Young, Bruce A.
ABSTRACT: Amphibious vertebrates, such as the water monitor ( Varanus salvator ), require anatomical and/or neural specializations to cope with pressure changes on the tympanic membrane when transiting between air and water. V. salvator has internally coupled ears which are distinguished by (patent) anatomical conduits through the skull linking the middle ear cavities on both sides of the head. We describe a small skeletal muscle in V. salvator which inserts onto the middle ear ossicle and the tympanic membrane. Laser doppler vibrometry demonstrates that contraction of this muscle both increases the vibrational velocity of the tympanic membrane and changes the waveform pattern of the tympanic displacement. The combined anatomical and functional results suggest that V. salvator is capable of actively modulating the tension of the tympanic membrane. Anat Rec, 299:1270–1280, 2016. © 2016 Wiley Periodicals, Inc.